Human N-Alpha-Acetyltransferase 60 Promotes Influenza A Virus Infection by Dampening the Interferon Alpha Signaling - Ahmed, Farjana; Husain, Matloob (Frontiers in Immunology, 2022)
N-alpha-acetyltransferase 60 (NAA60) is the most recently discovered N-terminal acetyltransferase and found only in multicellular eukaryotes. NAA60 localizes to the Golgi complex and is one of the only two N-terminal acetyltransferases known to localize to an organelle. Furthermore, NAA60 possesses a unique ability of catalyzing the acetylation of membrane-anchored proteins at the N-terminus and histones at the lysine side chains. Herein, we demonstrate that NAA60 exhibits proviral properties during influenza A virus (IAV) infection by interfering with the interferon (IFN) α signaling. We found that the depletion and overexpression of NAA60 reduced and enhanced, respectively, the IAV growth in a cell type- and IAV strain-independent manner. Mechanistically, the IAV-induced expression of IFNα was increased and decreased in NAA60-depleted and -overexpressing cells, respectively. Furthermore, the depletion of NAA60 enhanced the level of phosphorylated STAT1 transcription factor as well as the expression of several IFN-stimulated genes (ISGs) such as MX1, CH25H, IFITM3, ISG15 and viperin in infected cells. Whereas the overexpression of NAA60 produced opposite results. Finally, similar results were obtained when the NAA60-depleted cells were treated with purified IFNα. These findings, in conjunction with our recent findings where N-terminal acetylation of many host proteins increased in response to the IAV infection, indicate an important role of N-terminal acetylation during IAV replication.